1999
DOI: 10.1111/j.1600-0447.1999.tb10835.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the place of treatment influence the quality of life of schizophrenics?

Abstract: It is probably not the place per se which influences the QOL, but apart from personal, sociodemographic and illness-related factors, the amount of social support that is provided in different settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
14

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 15 publications
1
20
0
14
Order By: Relevance
“…Mentally ill people are, as surveys indicate, strongly dissatisfied about not working and many express their desire for competitive employment [3,7]. If they are asked what constitutes a good quality of life, psychiatric inpatients suffering from chronic schizophrenia mention most frequently social relationships and being employed [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Mentally ill people are, as surveys indicate, strongly dissatisfied about not working and many express their desire for competitive employment [3,7]. If they are asked what constitutes a good quality of life, psychiatric inpatients suffering from chronic schizophrenia mention most frequently social relationships and being employed [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…They showed educational level influenced the QOL. 24 Another study reported that low level education affected patients with schizophrenia's QOL that was lower educational level among 75.6% participants. 25 The study revealed that there were no statistically significant with age and overall QOL.…”
Section: Resultsmentioning
confidence: 99%
“…En relación con la influencia de los recursos residenciales, numerosas investigaciones señalan que éstas logran mayor estabilidad psicopatológica y salud física en los pacientes (Dorvil et al, 2005;Jones, Chesters, Flechter, 2003;Rössler et al, 1999). Dorvil y colaboradores (2005) indican que los recursos residenciales ofrecen espacios libres de juicios morales donde la experiencia de la enfermedad es aceptada.…”
Section: Recuperación Relaciones Personales Y Comunidadunclassified